HPV vaccine hesitancy among parents in Italy: a cross-sectional study - Giorgia Della Polla; Concetta Paola Pelullo; Francesco Napolitano; Italo Francesco Angelillo (Taylor & Francis Group, 2020)
This cross-sectional survey determined the vaccine hesitancy related to Human papillomavirus (HPV) and the determinants among parents of adolescents aged 12 and 13 years in Italy. Data was collected through a self-administered questionnaire. Two-thirds of the parents (66.7%) had heard of HPV infection and knew that the vaccination was a preventive measure. Parents who had vaccinated their child against the HPV were more likely to have this knowledge. The vast majority (88%) considered the immunization useful for the prevention of HPV-related cancers with an average value of 8.4. This positive attitude was higher among parents who had heard of HPV infection and knew that vaccination was a preventive measure, who had received information from physicians, who had vaccinated their child against the HPV, who were concerned that their child could contract the HPV infection, and who needed information on HPV vaccination. More than half (57.9%) self-reported that they had vaccinated their child against HPV and only 6.2% had delayed the administration of a dose. One-third (33.3%) were hesitant toward anti-HPV vaccination with a total Parent Attitudes about Childhood Vaccines Survey (PACV) score ≥50. Unmarried respondents, those who had not heard of HPV infection and did not know that the vaccination was a preventive measure, who did not believe that the vaccination was useful for the prevention of HPV-related cancers, and who needed information on HPV vaccination were more likely to be hesitant. Communication and education strategies must be undertaken to ensure that parents are fully informed and health-care professionals should provide materials with details regarding the risk of acquiring a HPV infection and vaccine usefulness.